Linking Technology Acceptance (TAM3) and Institutional Readiness (TOE) in Digital Public Fund Disbursement: Evidence from Indonesia’s Makan Bergizi Gratis (MBG) Program - Arliani Ivandhari; Sahat Hutajulu (Program Pascasarjana STIE Amkop Makassar, 2026)
Makan Bergizi Gratis (MBG) is an Indonesian government program to reduce stunting rates and strengthen nutritional quality. Badan Gizi Nasional (BGN) implemented technology adoption in the form of a Bank Rakyat Indonesia’s (BRI) Virtual Account (VA) to save time and increase transparency in fund distribution. The purpose of this study is to quantify, identify factors, and assess the contribution of the VA dashboard. This study introduces the TAM-TOE model approach as a theoretical model in the study of technology adoption. The Technology Acceptance Model (TAM3) focuses on a survey of perceived usefulness, ease of use, and behavioral intentions of SPGG officers and is analyzed using the SEM-PLS method. The Technology–Organization–Environment (TOE) study focused on technology adoption through interviews with BGN officials and analyzed using descriptive methods. The results showed that Virtual Accounts were proven to increase disbursement speed, reduce reconciliation errors, and strengthen audit accountability. SPPG officers reported increased confidence in managing daily transactions, in line with survey results showing positive perceptions regarding the benefits and ease of using VA. This is consistent with the SEM-PLS results showing that Behavioral Intention is significantly influenced by Perceived Usefulness (P-value = 0.000) and Perceived Ease to Use (P-value = 0.032). From an institutional perspective, BGN emphasized that the dashboard strengthens financial oversight and enhances accountability.